Epitope spreading phenomenon: A case report - Keerthana Krishnaswamy; Belliappa Pemmada Raju; Leena Raveendra (Indian Dermatology Online Journal, 2019)
The concomitant occurrence of psoriasis vulgaris (PV) and bullous pemphigoid in a patient is rare. We report a 55-year-old male, with history of PV since 4 years, on irregular topical medication, who developed multiple fluid-filled lesions all over the body. A combination treatment with prednisolone, cyclosporine, and dapsone followed by methotrexate was proved suitable and effective.